2008
DOI: 10.1002/acp.1526
|View full text |Cite
|
Sign up to set email alerts
|

How multiple external representations are used and how they can be made more useful

Abstract: In two studies, students' difficulties in using multiple external representations were effectively addressed. In a first explorative study (N ¼ 16), we investigated the allocation of visual attention (as assessed by gaze data) on external representations, its relation to learning and learners' beliefs on the representations' functions. Results confirmed that students were not aware of the functions. In a subsequent experiment (N ¼ 30), we analysed effects of informing students about the function of diagrams in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 12 publications
3
83
0
6
Order By: Relevance
“…Some of these difficulties can be attributed to the learners' limited knowledge of the roles or functions of external representations. For example, Schwonke, Berthold, and Renkl (2009) found that even advanced learners who studied worked examples with multirepresentational solutions (i.e., word problems accompanied by tree diagrams and equations) in the domain of 'probability' were largely unaware of the cognitive functions of these external representations (e.g., complementing or constraining interpretation of one another). In a subsequent intervention study, simply informing about the cognitive functions (especially of tree diagrams in the worked-out examples) led to deeper conceptual understanding of probability problems and better procedural skills in solving probability problems.…”
Section: Multiple External Representationsmentioning
confidence: 99%
“…Some of these difficulties can be attributed to the learners' limited knowledge of the roles or functions of external representations. For example, Schwonke, Berthold, and Renkl (2009) found that even advanced learners who studied worked examples with multirepresentational solutions (i.e., word problems accompanied by tree diagrams and equations) in the domain of 'probability' were largely unaware of the cognitive functions of these external representations (e.g., complementing or constraining interpretation of one another). In a subsequent intervention study, simply informing about the cognitive functions (especially of tree diagrams in the worked-out examples) led to deeper conceptual understanding of probability problems and better procedural skills in solving probability problems.…”
Section: Multiple External Representationsmentioning
confidence: 99%
“…It has also been used in various areas of educational psychology in a number of studies over recent years (e.g. Vauras et al 1992;Schwonke et al 2009;Verschaffel et al 1992). There has recently been increased interest in this methodology, especially in research about multimedia learning (Mayer 2010;Scheiter and van Gog 2009;van Gog and Scheiter 2010) and expository text reading (Hyönä et al 2002;Hyönä and Nurminen 2006).…”
Section: Eye Movements and Text Readingmentioning
confidence: 99%
“…Often, coding and rating schemes are used to analyze recorded CSIC sessions and log-files post-hoc, in order to classify a wide range of learning-related activities (Wittwer, Nückles, & Renkl, 2010). These may be complemented by online measurements such as eye-movement data (Schwonke, Berthold, & Renkl, 2009), think-aloud protocols (Ericsson, 2003), or measures of cognitive load (Eysink, de Jong, Berthold, Kolloffel, Opfermann, & Wouters, 2009). …”
Section: Learning Perspective Methodsmentioning
confidence: 99%